Optimalisasi Masyarakat Desa Dalam Menghadapi Tanggap Darurat Pandemi Covid-19 - Putri , Elfirda Ade; Pribadi, Slamet (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
The lack of public awareness of the implementation of the Covid-19 health protocol has made the spread of Covid-19 even more massive, for example on December 1, 2020 in our country Indonesia has reached 543,975 positive cases with 17,081 deaths and 454,879 recoveries and if we refer to the data on CoronaVirus cases in the world, it has reached 2,500 cases. positive 63,315,184 with 1,469,835 deaths and 40,602,957 recoveries. The data was obtained from the Johns Hopkins Coronavirus Resource Center. This activity provides education to the people of Lubang Buaya Village on the importance of wearing masks, washing hands and maintaining distance as well as providing education to the community about the dangers of the Covid-19 virus and providing benefits to the community on the importance of preventing the spread of Covid-19 in the form of counseling.